Variations in the SDN Loop of Class A Beta-Lactamases: A Study of the Molecular Mechanism of BlaC (Mycobacterium tuberculosis) to Alter the Stability and Catalytic Activity Towards Antibiotic Resistance of MBIs - Bhattacharya, Sourya; Junghare, Vivek; Pandey, Niteesh Kumar; Baidya, Subhecchha; Agarwal, Harsha; Das, Neeladrisingha; Banerjee, Ayan; Ghosh, Debashish; Roy, Partha; Patra, Hirak K.; Hazra, Saugata (Frontiers in Microbiology, 2021)
The emergence of multidrug-resistant (MDR) and extensively drug-resistant (XDR) tuberculosis calls for an immediate search for novel treatment strategies. Recently, Blac, the principal beta-lactamase of Mycobacterium tuberculosis, was recognized as a potential therapeutic target. Blac belongs to Ambler class A, members of which are generally susceptible to the beta-lactamase inhibitors currently used in clinics: Tazobactam, Sulbactam, and Clavulanate. Alterations at Ser130 in conserved SDN loop confer resistance to mechanism-based inhibitors (MBIs) commonly observed in various clinical isolates. The absence of clinical evidence of S130G conversion in Mycobacterium tuberculosis draws our attention to built laboratory mutants of S130G and S130A of Blac. The study involving steady-state, inhibition kinetics, and fluorescence microscopy shows the emergence of resistance against MBIs to the mutants expressing S130G and S130A. To understand the molecular reasoning behind the unavailability of such mutation in real life we have used circular dichroism (CD) spectroscopy, differential scanning calorimetry (DSC), molecular dynamics (MD) simulation, and stability based enzyme activity to compare the stability and dynamic behavior of native and S130G/A mutant form of Blac. A significant decrease in melting temperature (Blac Tm 60°C, S130A Tm 50°C, S130G Tm 45°C), kinetic instability at higher temperature and comparative dynamic instability correlate the fact that resistance to beta-lactam-beta-lactamase inhibitor combinations will likely not arise from the structural alteration of Blac, therefore establishing conﬁdence that this therapeutic modality can be potentially applied as a part of a successful treatment regimen against M. tuberculosis.